Effects of bolting and flower stem removal on the growth and chemical qualities of onion bulbs - Kwon, Young Seok; Kim, Cheol Woo; Kim, Ji Sun; Moon, Jin Seong; Yoo, Kil Sun (Horticulture, environment and biotechnology, 2016)
The growth of a flower stem (bolting) causes a decrease in yield and marketability in onion. We have examined the effects of bolting and of the removal of flower stems at different lengths on the growth and chemical qualities of onion bulbs. Two onion cultivars, ‘Mapshihwang’ (M) and ‘Yeongmihwang’ (Y), were grown in the field and allowed to bolt. The treatments included the removal of three different lengths of the flower stem (short, medium, or long), uncut flower stem until harvest, or unbolted plants (control). Bolting and the length of the flower stem removed had no effect on bulb diameter but caused a decrease in bulb weight. The flower stems were generated after three to five scales; bolting and flower stem removal reduced the number of scales by approximately one scale. The total soluble solid content (SSC) and the total sugar content were also unaffected by bolting and the length of the flower stem removed. The pungency of the M and Y cultivars, being an average of about 5.0 and 2.8 μmol·mL -1 pyruvic acid, respectively, was not changed. The total quercetin content showed various responses to the treatments and no clear differences compared to the unbolted bulbs. The total phenolic content was not changed by bolting or the stem removal treatments. In conclusion, bolting and removal of the flower stem caused a decrease in bulb weight, whereas the SSC, total sugar content, pungency, quercetin content, and total phenolic content remained unaffected, indicating that the chemical qualities of the bolted bulbs was identical to those of the unbolted, normal bulbs. The removal time of the flower stem had no significant difference on bulb quality.